2016
DOI: 10.3945/jn.115.222547
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid Supplementation in Postpolypectomy Patients in a Randomized Controlled Trial Increases Tissue Folate Concentrations and Reduces Aberrant DNA Biomarkers in Colonic Tissues Adjacent to the Former Polyp Site

Abstract: A response to folic acid supplementation, which increased colonocyte folate and improved folate-related DNA biomarkers of cancer risk, was seen in the participants studied. Exploratory analysis points toward the area formerly adjacent to polyps as possibly driving the response. That these areas persist after polypectomy in the absence of folate supplementation is consistent with a potentially carcinogenic field's causing the appearance of the polyp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…Five percent of this population has intakes exceeding the UL of 1,000 mcg per day. This is thought mainly due to folic acid from dietary supplements [40]. One thousand mcg daily is thought excessive because some but not all literature suggests that high dose folic acid increases colon and prostate cancer risk [39].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Five percent of this population has intakes exceeding the UL of 1,000 mcg per day. This is thought mainly due to folic acid from dietary supplements [40]. One thousand mcg daily is thought excessive because some but not all literature suggests that high dose folic acid increases colon and prostate cancer risk [39].…”
Section: Commentmentioning
confidence: 99%
“…One thousand mcg daily is thought excessive because some but not all literature suggests that high dose folic acid increases colon and prostate cancer risk [39]. However, a recent study suggests 600 mg a day of folic acid reduces DNA biomarkers of cancer adjacent to colon polyp sites [40]. After multivariate adjustment, a recently published study in female US nurses showed a non-statistically significant increased risk of psoriasis to the subgroup having low dietary folate equivalent (DFE) intake among those drinking over 5 nonlight beers per week as compared to the high DFE group in this study.…”
Section: Commentmentioning
confidence: 99%
“…Folate and folic acid are rich in fruits including oranges, lemons, bananas, melons and strawberries. The randomized controlled trial conducted at Dublin hospital from O'Reilly's study demonstrated that decreased vitamin B level was associated with increased risks of colon cancer [122]. It was reported that the inverse association between vitamin B level and risk of colon cancer was related to genomic instability (mis-incorporated uracil, DNA single strand breakage and DNA repair capacity) in response to vitamin level (deficient or supplemented) in different in-vitro cell studies, rodent models and human case-control studies [123].…”
Section: Colon Cancermentioning
confidence: 99%
“…In all cases the malignant transformation was related to a significant decrease of SAM and global DNA hypomethylation, especially in DNA sequences where oncogenes are codified. In contrast, folic acid supplementation improved folate-related DNA biomarkers of cancer risk in colonic tissues adjacent to the former polyp site (Figure 2) [8]. Functional Food -Improve Health through Adequate Food…”
Section: Folatesmentioning
confidence: 99%